THE GAMES AND THEIR USAGE IN ENGLISH CLASROOMS AT SCHOOL. (Лучшие интеллектуальные исследования, 2025)
Abstract: This article explores the role of games in enhancing the effectiveness of English language instruction in school classrooms. With the growing need for communicative and student-centered approaches, games have become valuable tools for motivating learners, encouraging interaction, and reinforcing language skills in a fun and engaging way. The study examines different types of educational games—such as vocabulary games, grammar puzzles, role-plays, and interactive group activities—and analyzes their impact on students’ motivation, participation, and language retention. Data were collected through   classroom observations, teacher interviews, and student feedback in several primary and secondary schools. Findings indicate that well-structured games not only make learning enjoyable but also promote collaborative learning and improve students’ speaking, listening, reading, and writing skills. The article concludes by offering practical suggestions for English language teachers on how to effectively integrate games into their lesson plans to enhance learning outcomes.